Clinicial-pathologic correlations of non-trauma related Odontodysplasia in 28 dogs: 2013-2023 - Kot, Ching Ching Shirley; Goldschmidt, Stephanie; Vapniarsky, Natalia; Arzi, Boaz; Soltero-Rivera, Maria (Frontiers in Veterinary Science, 2024)
Odontodysplasia is an uncommon dental developmental disorder associated with enamel, dentin, pulp abnormalities, and overall tooth morphology. The affected tooth is grossly abnormal in size and contour and is commonly associated with swelling of the affected area and failure of eruption. Histologically, the enamel and dentin are hypoplastic and hypomineralized. Odontodyplasia occurs most commonly in response to direct trauma to the developing tooth bud (enamel organ and dental follicle). Data on the prevalence and features of non-traumatic odontodysplasia are lacking. Medical records of dogs diagnosed with odontodysplasia were reviewed at the William R. Pritchard Veterinary Medical Teaching Hospital (VMTH), University of California, Davis, for ten years (from 2013 to 2023). Dogs with a known history of facial trauma, persistent deciduous tooth or teeth over the region of odontodysplastic tooth or teeth, and endodontic disease of the persistent deciduous tooth or teeth were excluded from the study. Twenty-eight dogs were included in this retrospective study, representing an incidence of 1.4 per 100 dogs presenting over ten years. Regional odontodysplasia (RO) was identified in twenty-two dogs, and generalized odontodysplasia (GO) was found in six dogs. Both comprehensive oral examination and diagnostic imaging were essential in diagnosing and assessing the presence of odontodysplasia. Awake oral examination failed to identify odontodysplasia in almost 70% of the RO cases. Secondary diseases or lesions in odontodysplastic teeth, such as periodontal disease, endodontal disease, and perio-endo lesions, were commonly seen and were particularly more frequently identified in strategic teeth (canine and carnassial teeth) than non-strategic ones. Similarities, such as female predilection, maxilla more commonly affected, and clinical signs, were observed between RO in dogs and those reported in people. The exact etiology of non-traumatic odontodysplasia remains elusive, and the condition may be of multifactorial causality.